MUJAMIL QOMAR’S PERSPECTIVE ON RELIGIOUS MODERATION AND ITS IMPLEMENTATION FOR THE MUSLIM COMMUNITY IN INDONESIA - Mochammad Nginwanun Likullil Mahamid (Profetika: Jurnal Studi Islam, 2022)
This article attempted to find out Mujamil Qomar's perspective on religious moderation and its implementation for the Muslim community in Indonesia, which was increasingly needed by the Indonesian people. This article aimed to provide an understanding to readers of the importance of instilling the spirit of religious moderation taught by experts in the field of Islamic education and thought. This article was written using a unit analysis study in a book entitled "Moderasi Islam Indonesia: Wajah Keberagaman Progresif, Inklusif, dan Pluralis" written by Mujamil Qomar. Then, several book reviews with the same discussion on religious moderation were added to compare, complement, and continue discussions that have not been discussed in previous books. The important findings of this article explained that religious moderation was a means to select Islamic thoughts, understandings, and practices carried out in the form of violence or radicals. In addition, the researcher wanted to provide a positive view of religious moderation in Indonesia, where the Muslim community appeared very elegant, egalitarian, flexible in socializing, and able to accept opinions from people of different faiths.